Pengaruh Return on Equity (ROE), Price Earning Ratio (PER), dan Debt to Equity Ratio (DER) Terhadap Return Saham Pada Sektor Consumer Goods Industry yang Terdaftar di Bursa Efek Indonesia - Wita Putri Verta; Elvi Rahmi (Universitas Negeri Padang, 2021)
This study to determine: (1) the effect of return on equity on stock returns in consumer goods industry sector companies listed on the IDX in 2010-2018, (2) the effect of price earning ratio on stock returns in consumer goods industry sector companies listed on the IDX in 2010-2018, (3) the effect of debt-to-equity ratio on stock returns in consumer goods industry sector companies listed on the IDX in 2010-2018. This research as causative research classified. This study in population were all companies in the consumer goods industry sector listed on the IDX in 2010-2018, 50 companies totaling. This study in sample were 15 companies which determined by purposive sampling method. The type of data used is secondary data, namely financial statements of companies in the consumer goods industry sector which are sourced from the official website of the IDX, ICMD using the documentation method. The analysis used was the chow test, hausmant test, lagrange test, panel regression analysis, determination coefficient (R2), F test and t test using the Eviews v.10 program. The test results show that (1) ROE has a positive and significant effect on stock returns in the consumer sector companies’ goods industry on the IDX in 2010-2018 (2) PER has a negative and significant effect on stock returns in the consumer sector companies’ goods industry on the IDX in 2010-2018 (3) DER has a negative and significant effect on stock returns in the consumer sector companies’ goods industry on the IDX in 2010-2018. So that shareholder can use ROE, PER and DER as one of the factors that affect stock returns. Meanwhile, further researchers are expected to expand the research by increasing the population and research samples and adding independent variables which are considered to affect stock returns.Keywords: stock return, return on equity, price earning ratio, debt equity ratio